2009
DOI: 10.1016/j.jelekin.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A bi-dimensional index for the selective assessment of myoelectric manifestations of peripheral and central muscle fatigue

Abstract: Two physiological factors are assumed in this paper to mainly determine the myoelectric manifestations of fatigue: (1) the decrease of the conduction velocity (CV) of motor unit action potentials (MUAP) (peripheral fatigue), and (2) the increase of MU synchronization by the central nervous system (central fatigue). To describe separately the peripheral and central components of the myoelectric manifestations of fatigue, we investigated the following indexes: (1) mean spectral frequency - MNF, (2) median spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 58 publications
(62 reference statements)
8
114
0
2
Order By: Relevance
“…A recent study has suggested that the CV, MF, and RMS are more sensitive to peripheral fatigue [29]. Therefore, our CV, MF, and RMS results suggest VE, especially at 30 Hz, to produce a larger degree of peripheral fatigue as compared to control condition.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…A recent study has suggested that the CV, MF, and RMS are more sensitive to peripheral fatigue [29]. Therefore, our CV, MF, and RMS results suggest VE, especially at 30 Hz, to produce a larger degree of peripheral fatigue as compared to control condition.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the vibrationinduced fatiguing effect to the central nervous system should also be taken into consideration. In this study, the FD was estimated as an indicator for the central fatigue, as suggested by a recent study [29]. In ( [29]), the FD was found to decrease with increasing motor-unit synchronization, in silico, and during sustained contraction, in in − vivo [29].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although many medical diagnosis methods can be use to survey the health state of the astronaut, however the size and the endurance time of the muscle force [2] can reflect the health state of a person directly. One of merits of the force analysis method consists that the muscle force can show us the integrated health state of people [3] such as the physiological health and the psychological health. Another virtue is that the muscle forces are very easy to measure.…”
Section: Introductionmentioning
confidence: 99%